Business Validation Using Disciplined Entrepreneurship Framework for Lokaly95 (The Indonesian Journal of Business Administration, 2021)
Asia has grown to become the largest and most populous of the continents since 1960 (Cox, 2018). International Enterprise Singapore (2013) stated that strong domestic demand is expected to underpin Indonesia's GDP growth, as the share of private consumption is predicted to rise from 56% in 2012 to 65% in 2030. Furthermore, Indonesia is the largest foodservice market among all ASEAN countries (Agriculture and Agri-Food Canada, 2016). The study found that as far as trends for foodservice growth, there's a strong indication that the world is fast becoming a cafe-centric place, with the cafe category found to be the fastest-growing menu category globally, showing 9.9 percent sales growth in 2016 (Qsrweb.com, 2018). With the development of the foodservice industry, the industry needs to pay attention to consumers. The cafe industry has various influencing factors in providing services for customer satisfaction. Sugianto and Sugiharto (2013) also stated that service quality significantly affects customer satisfaction, especially on employees' speed and responsiveness in serving customers. Responsiveness in cafe and restaurant services is essential so that it is related to the operation of cafes and restaurants in serving food and beverages. The duration of cooking and its material are important aspects in cafes operational, so that the industry needs to pay attention to the right product and its development for consumers. The product in single packing and ready to cook can speed up the duration of serving. Also, the efficiency of the ingredients' use and effectiveness in calculating costs are aspects offered by the single packing product. So, Lokaly95 comes with products that can meet these needs. Besides, there are challenges facing restaurant operators in third party partnerships that are both necessary and expected (Euromonitor International, 2018). So this study provides research on how Lokaly95 can meet the exact market needs and calculations regarding market availability sufficient for Lokaly95 to consider. This study also validates the initial idea about Lokaly95 that needs to be tested to provide an overview of managing and planning Lokaly95 in the future.This research uses a disciplined entrepreneurship framework that adjusts the academic final project format. This research step is through exploration, solution, and making an implementation plan. This study is developed through initial ideas. Then explores the idea and validates it through observation, interview, and fill in the questionnaire. Exploration solves a consideration for the implementation plan. The result of this research is a coffee shop as Lokaly95 market with frozen food products that are packaged per portion as the Lokaly95 value. Lokaly95 products consist of 20 types based on end-customer validation. The implementation plan is formed based on the acquiring customer process. Keywords: Frozen Food, Coffee Shop Supplier, Business Validation.